Understanding bacterial pathogenicity: a closer look at the journey of harmful microbes - Soni, Jyoti; Sinha, Sristi; Pandey, Rajesh (Frontiers in Microbiology, 2024)
Bacteria are the most prevalent form of microorganisms and are classified into two categories based on their mode of existence: intracellular and extracellular. While most bacteria are beneficial to human health, others are pathogenic and can cause mild to severe infections. These bacteria use various mechanisms to evade host immunity and cause diseases in humans. The susceptibility of a host to bacterial infection depends on the effectiveness of the immune system, overall health, and genetic factors. Malnutrition, chronic illnesses, and age-related vulnerabilities are the additional confounders to disease severity phenotypes. The impact of bacterial pathogens on public health includes the transmission of these pathogens from healthcare facilities, which contributes to increased morbidity and mortality. To identify the most significant threats to public health, it is crucial to understand the global burden of common bacterial pathogens and their pathogenicity. This knowledge is required to improve immunization rates, improve the effectiveness of vaccines, and consider the impact of antimicrobial resistance when assessing the situation. Many bacteria have developed antimicrobial resistance, which has significant implications for infectious diseases and favours the survival of resilient microorganisms. This review emphasizes the significance of understanding the bacterial pathogens that cause this health threat on a global scale.